Effect of the phosphodiesterase 4 inhibitor apremilast on cardiometabolic outcomes in psoriatic disease—results of the Immune Metabolic Associations in Psoriatic Arthritis study. (7th June 2021) - Ferguson, Lyn D; Cathcart, Susanne; Rimmer, Dominic; Semple, Gary; Brooksbank, Katriona; Paterson, Caron; Brown, Rosemary; Harvie, John; Gao, Xuan; Radjenovic, Aleksandra; Welsh, Paul; McInnes, Iain B; et al.
Abstract: Objectives: Studies have suggested phosphodiesterase 4 (PDE4) inhibition may be associated with weight loss and other cardiometabolic benefits. We evaluated the effect of the PDE4 inhibitor apremilast on body weight and composition, glucose homeostasis, lipid profiles and vascular function in psoriatic disease and whether weight change correlated with therapeutic response. Methods: We conducted a prospective, open-label study (Immune Metabolic Associations in Psoriatic Arthritis) of adults receiving apremilast 30 mg as part of routine care for PsA and/or psoriasis. Cardiometabolic, anthropometric and disease activity assessments were performed at baseline (pre-apremilast) and at months 1, 3 and 6 of apremilast treatment in 60 patients. A subgroup underwent further assessment of endothelial function, body composition and adipocyte morphology. Results: In patients (median age 54.5 years, 63% women, median BMI 33.2 kg/m 2 ), apremilast was associated with a mean weight loss of 2.2 kg (95% CI 1.4, 3.0; P < 0.001) and a mean BMI decrease of 0.8 kg/m 2 (95% CI 0.5, 1.2; P < 0.001) after 6 months of treatment. Body composition analysis demonstrated a reduction in total abdominal fat [mean decrease 0.52 L (95% CI 0.08, 0.96), P = 0.022], principally subcutaneous adipose tissue [mean decrease 0.37 L (95% CI 0.05, 0.68), P = 0.022]. There was no change in adipocyte diameter, haemoglobin A1c, lipid, glucagon-like peptide-1 or vascular function. Psoriatic disease activity improved with apremilast, although this was not correlated with weight change. Conclusion: Following apremilast treatment, we observed weight loss, principally abdominal subcutaneous fat, and improvement in psoriatic disease activity. The latter was independent of weight change, suggesting apremilast likely acts through direct immunological mechanisms.